Atividade antibacteriana do óleo essencial de Citrus limon frente cepas multidroga resistentes do gênero Acinetobacter. - Guerra, Felipe Queiroga Sarmento (2012)
Acinetobacter species have gained importance in recent years due to their increased involvement in serious infections and antimicrobial resistance. Since multidrug resistant bacteria pose a challenge to the treatment of infections, it is necessary to find new substances with antimicrobial properties in combating these microorganisms. Thus, medicinal plants are studied, since they are used for treatment of various illnesses. Therefore, many studies on biological activity have been performed with essential oils obtained from medicinal plants, such as the essential oil from Citrus limon (EOCL), attempting to help overcome this problem. Thus the present study aimed to evaluate the effect of the essential oil of EOCL against multidrug resistant strains of Acinetobacter spp. Its chemical composition was determined by GC/MS and its antibacterial activity was assessed by determining their MIC and MBC by microplate bioassay, its Time kill too was determinated. Also was analyzed the effect of modulating action of conventional antibiotics by microplate bioassay. Among phytochemicals, Neral (29.4%) presented as the major essential component of EOCL. The oil caused growth inhibition in 16 (67%) of 24 strains tested, showing a MIC of 625 μg/ml and MBC of 1250 μg/mL. In a time kill study, the oil displayed a concentration-dependent antibacterial activity. Results of combining antibiotics and EOCL had shown us a synergistic and additive effect with EOCL /antibiotics combinations. The results of this study suggest that essential oil of C. limon may suppress the growth of Acinetobacter species and could be a source of metabolites with modified antibacterial activity.